The "Good fella missus" - Turner, V. E. (Violet Elizabeth); United Aborigines Mission (Adelaide : United Aborigines Mission, 1938)
Account of the work of Miss Annie Lock of the United Aborigines Mission; (Central Australia)
Keywords: Lock, Annie, -- 1876-1943.; United Aborigines Mission; Missions -- Northern Territory; Aboriginal Australians -- Northern Territory -- Missions; Aboriginal Australians -- Missions -- Northern Territory; Northern Territory - Central NT